An all-dielectric metasurface as a broadband optical frequency mixer - Sheng Liu (Nature Portfolio, 2018)
Frequency mixers are hard to achieve at optical frequencies because it is difficult to meet different phase-matching conditions. Here, the authors show that GaAs metasurfaces can mix laser beams to generate eleven new wavelengths through different nonlinear optical processes occurring simultaneously.